PENGARUH KUALITAS PELAYANAN, PERSEPSI NILAI, DAN PERSEPSI KEGUNAAN, TERHADAP MINAT BERKELANJUTAN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING (Studi Pada Pengguna Dompet Digital (e-Wallet) OVO di Kota Semarang) - Pangestu MT, M. Adjie; Sukresna, I Made (Diponegoro Journal of Management, 2021)
The development of the internet in the world is getting wider so that many companies are trying to create products and services to meet people's wants and needs. Companies must create new marketing strategies in order to survive and attract larger consumers. This study aims to determine the effect of service quality, perceived value, and perceived usefulness on continuance intention with customer satisfaction as an intervening variable. The population in this study were users of the OVO digital wallet (e-Wallet) who had used OVO to make purchase transactions. The number of samples used were 160 respondents and were selected by purposive sampling and data collection methods through questionnaires. The analytical tool used in this research is the AMOS program.The results of this study indicate that service quality, perceived value, and perceived usefulness have a positive and significant effect on customer satisfaction. Furthermore, customer satisfaction also has a positive and significant effect on continuance intention. The process that has the most influence on increasing continuance intention on OVO digital wallets (e-Wallets) is an increase in service quality that affects customer satisfaction as a determinant of success in increasing continuance intention.